Perbedaan Pengaruh Pemberian Transcutaneus Electrical Nerve Stimulation (TENS) Dengan Pen Elektrode Dan TENS Dengan Pad Elektrode Terhadap Pengurangan Nyeri Pada Low Back Pain Myogenik Di Rumah Sakit Medika Mulia Tuban - Kristipi Dwirianawati; Achmad Fariz; Retno Dewi Prisusanti; Agung Hadi Endaryanto (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Myogenic low back pain (LBP) is often caused by musculoskeletal disorders such as muscle stiffnes, muscle spasme due to impoper body movements. LBP can be given Physiotherapy modalities in the form of Transcutaneus Electrical Nerve Stimulation (TENS)with current parameters and the use of predetermined electrode such as the use of TENS with a pen electrode and TENS with an electrode pad. This study aims to determine the difference in the effect of administering TENS with pen electrode an TENS with electrode pads on the reduction of Myogenic LBP pain using the Visual Analoque Scale (VAS) measuring instrument Methods: The type of research usedis a quasi experimental with two groub pretest-posttest design. The sampling process in this study use purposive sampling. The number of samples was 34 people with 17 people being given TENS with a pen electrode and 17 people being given TENS with a pad electrode for 3 weeks with intervention therapy 2 times a week.Results: The results of the analysis test with the chi square test showed of p > 0,05 with a different mean value in the VAS measurement of the TENS action with the pen electrode of 0.882 procedure. While the mean different value in the VAS measurement of the TENS action with the electrode pad shows a value of 0.764 action.Conclusion: The conclusion of this study shows that presenting TENS with pen electrodes is effective in reducing pain in myogenic LBP compered to TENS with electrode pads.